Modulation of spontaneous locomotor and respiratory drives to hindlimb motoneurons temporally related to sympathetic drives as revealed by Mayer waves - Wienecke, Jacob; Enríquez Denton, Manuel; Stecina, Katinka; Kirkwood, Peter A.; Hultborn, Hans (Frontiers in Neural Circuits, 2015)
In this study we investigated how the networks mediating respiratory and locomotor drives to lumbar motoneurons interact and how this interaction is modulated in relation to periodic variations in blood pressure (Mayer waves). Seven decerebrate cats, under neuromuscular blockade, were used to study central respiratory drive potentials (CRDPs, usually enhanced by added CO2) and spontaneously occurring locomotor drive potentials (LDPs) in hindlimb motoneurons, together with hindlimb and phrenic nerve discharges. In four of the cats both drives and their voltage-dependent amplification were absent or modest, but in the other three, one or other of these drives was common and the voltage-dependent amplification was frequently strong. Moreover, in these three cats the blood pressure showed marked periodic variation (Mayer waves), with a slow rate (periods 9 - 104 s, mean 39 ± 17 SD). Profound modulation, synchronized with the Mayer waves was seen in the occurrence and/or in the amplification of the CRDPs or LDPs. In one animal, where CRDPs were present in most cells and the amplification was strong, the CRDP consistently triggered sustained plateaux at one phase of the Mayer wave cycle. In the other two animals, LDPs were common, and the occurrence of the locomotor drive was gated by the Mayer wave cycle, sometimes in alternation with the respiratory drive. Other interactions between the two drives involved respiration providing leading events, including co-activation of flexors and extensors during post-inspiration or a locomotor drive gated or sometimes entrained by respiration. We conclude that the respiratory drive in hindlimb motoneurons is transmitted via elements of the locomotor central pattern generator. The rapid modulation related to Mayer waves suggests the existence of a more direct and specific descending modulatory control than has previously been demonstrated.